2020
DOI: 10.3747/co.27.5401
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Anal Cancer Screening Tests for Women Living with HIV in the EVVA Study

Abstract: Background Anal cancer is potentially preventable through screening. For screening to be implemented, the screening procedures must be acceptable to the affected population. The objective of the present study was to measure the acceptability of currently available anal cancer screening tests in a population of women living with hiv who had experienced the tests.Methods The evva study (“Evaluation of Human Immunodeficiency Virus, Human Papillomavirus, and Anal Intraepithelial Neoplasia in Women”) is a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“…The high proportion of abnormalities on both anal cytology and HRA could also indicate underscreening in our clinic population. Qualitative studies have shown that anal cytology and HRA are feasible and acceptable to most PWH [ 23 , 24 ]. However, barriers to screening still exist, such as stigma, lack of awareness about HPV, and psychological discomfort associated with anal cancer screening [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of abnormalities on both anal cytology and HRA could also indicate underscreening in our clinic population. Qualitative studies have shown that anal cytology and HRA are feasible and acceptable to most PWH [ 23 , 24 ]. However, barriers to screening still exist, such as stigma, lack of awareness about HPV, and psychological discomfort associated with anal cancer screening [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EVVA study (“Evaluation of HIV, HPV, and AIN in Women”) is a prospective observational cohort study, which followed 151 WLHIV attending study visits every 6 months for 2 years [ 17 , 18 ]. Between January 2012 and July 2015, participants were recruited during routine HIV care at four HIV clinics in Montreal, Canada (McGill University Health Centre (MUHC), Clinique Médicale l’Actuel, Centre Hospitalier de l’Université de Montréal, and Clinique OPUS).…”
Section: Methodsmentioning
confidence: 99%
“…In one study, 87% of participants rated digital anal rectal examination as ".10 (very acceptable; so easy I would do it even more often)." 97 (See Appendix 7, http://links. lww.com/AOG/D275, for complete evidence summary.…”
Section: Techniques For Evaluationmentioning
confidence: 99%